Kourotrophia and "Mothering" Figures: Conceiving and Raising an Infant as a Collective Process in the Greek, Etruscan, and Roman Worlds : Some Religious Evidences in Narratives and Art - Pedrucci, Giulia (Open theology, 2020)
The paper deals with significantly different sources and historical periods: the parts dedicated to breastfeeding are based on votive statuettes of adults with infant/s from ancient Latium and Southern Etruria; the ones on pregnancy and childbirth are based on two archeological sources - one from Southern Etruria and one from Imperial Rome - which show the male (divine) appropriation of exclusively female biological functions; The parts on mothering are based on the concept of "mothering figures" (male mothering, animal mothering…) through mythological examples from Greek, Etruscan, and Roman art and narratives. Despite the heterogeneous documentation, we may conclude that the mother was not the only active character in the process of conceiving, giving birth, breastfeeding, and raising an infant in the Greek, Etruscan, and Roman societies. Many other figures close to the mother - male and female - were engaged in obtaining divine protection for her and her child; in helping, supporting, and even substituting her when necessary (and, of course, when possible). The research has been conducted mainly by using the concept of kourotrophia and mothering figures as analytical tools.